The female body in medicine and literature - Mangham, Andrew, 1979-; Depledge, Greta (Liverpool University Press, 2011)
This title features essays that explore literary texts in relation to the history of gynaecology and women's surgery. It demonstrates how fiction and medicine have a long-established tradition of looking towards each other for inspiration and elucidation in questions of gender.